Enhancing Cultural Competence in Ethnopsychiatry: A Systematic Review of Evidence-Based Strategies for Nursing Practice - Fatma Lutfiyatus Sayyida; Indi Dwi Shofi Yanti; Anggun Novia Indah Fitri (Interdisciplinary Journal of Ethnopsychiatric Nursing, 2025)
Cultural competence has become a critical component of effective and equitable mental health care, particularly in ethnopsychiatry, where cultural beliefs and practices significantly influence diagnosis, treatment, and therapeutic relationships. This systematic review aimed to identify and synthesize evidence-based strategies that enhance cultural competence among nurses working in psychiatric settings. Using the PRISMA framework, a comprehensive search was conducted across multiple academic databases, focusing on peer-reviewed studies published between 2012 and 2025. The review included interventions related to education, communication, technology, and systemic reform. Through thematic analysis, nine core strategies were identified: continuous education and training, experiential learning, technology-based tools, patient-centered inquiry, intercultural communication skills, assessment and measurement tools, curriculum integration, cultural matching and consultation services, and addressing systemic inequities and biases.While the strength of evidence for each strategy varied, their collective synthesis highlights the need for a multifaceted approach to developing cultural competence in nursing practice. These strategies not only improve clinical outcomes but also foster trust, reduce disparities, and support inclusive healthcare environments. Implementation requires institutional support, interdisciplinary collaboration, and policy alignment to ensure sustainability and impact. Integrating these strategies into nursing education and clinical practice will better equip nurses to meet the needs of increasingly diverse patient populations. By prioritizing cultural competence, the nursing profession can contribute meaningfully to equitable and high-quality mental health care delivery.